Relationship between markers of metabolic control and inflammation on severity of periodontal disease in patients with diabetes mellitus - L. P. Lim (Blackwell Synergy, 2007)
Aim: The aim of this study was to investigate the relationship between markers of metabolic control and inflammation and periodontal disease parameters in patients with diabetes. Material & Methods: One hundred and eighty one adult patients with diabetes attending treatment at two diabetes centres were invited to participate in the study. Periodontal examination included full-mouth assessment for probing depths and bleeding on probing (BOP). Blood analyses were carried out for glycated haemoglobin, (HbA1c), high-sensitivity C reactive protein, (hsCRP) and lipid profile comprising total cholesterol, low-density lipoprotein cholesterol (LDL chol), high-density lipoprotein cholesterol (HDL chol) and triglycerides. Results: Upon multivariate analysis, periodontal disease severity in terms of increased percentage of BOP and mean percentage of sites with probing depthsX5mm were found to be associated with inadequate glycaemic control as measured by HbA1c ( po0.01). HsCRP was also found to be a significant predictor for mean percentage of sites with probing depths X5mm ( po0.05). After controlling for age, gender, smoking habits and number of teeth, positive correlations were found between HbA1c and percentage sites with probing depths X5mm, percentage sites BOP, total cholesterol, LDL chol and triglycerides ( po0.05). Using the adjusted differences, subjects with acceptable glycaemic control (HbA1c o8%) showed a lower percentage of sites with BOP and probing depths X5mm(po0.05) when compared with those having inadequate glycaemic control. There was also a trend towards lower blood cholesterol in the well-controlled group. Conclusion: The level of glycaemic control as measured by HbA1c emerged as the most consistent risk factor associated with the extent and severity of periodontal disease in this study cohort.